The Influence Of Intellectual Capital And Organisational Learning Capability On The Competitive Capabilities Of Manufacturing Small And Medium Enterprises (Smes) In Malaysia - Theresa, Ho Char Fei (2013)
This research examined the relevance of intellectual capital in the context of manufacturing SMEs in Malaysia and how intellectual capital can enhance manufacturing competitive capabilities through organisational learning capability from the dynamic capability perspective. This research also investigates the relationship between manufacturing competing capabilities and business performance. In addition, it also examined how dynamic environment moderates the relationship between competitive capabilities and business performance. Data were collected from 145 manufacturing SMEs via survey questionnaire developed from related literature and interviews from practitioners. The data collected were then analysed using structural equation modeling via Smart PLS. Findings indicate that intellectual capital in terms relational and organisational capital had significant impact on organisational learning capability. Organisational learning capability mediates the relationship between intellectual capital (relational and organisational capital) and manufacturing competitive capabilities in terms of delivery dependability, flexible product innovation and quality. As for the relationship between manufacturing competitive capabilities and business performance, this study found quality have a significant impact on financial performance. This study also found that there is a significant positive relationship between non-financial performance and competitive capabilities (delivery dependability and quality). Moderating effect of dynamic environment on the relationship between competitive capabilities (delivery dependability and quality) and financial performance were found in this research. Theoretical and practical contributions of the research findings were discussed. Limitations of the research were explained and suggestions for future research were also presented.